Assessment of venom variation and phylogenetic relationships of Micrurus dumerilii from three different regions of Colombia (2025)
In the Americas, the genus Micrurus (coral snakes) includes the highest number of snake species, and Colombia is the second country with the greatest species diversity. Micrurus dumerilii has wide distribution and clinical importance in the country. The variability of its venom has not been extensively studied, and this could have implications for the neutralization by antivenoms. In this study, we explored the phylogenetic relationships between specimens from three regions of Colombia (Antioquia, Choco, and Santander) and the variation in their venoms using proteomics, in vitro and in vivo assays, and assessment of antigenic recognition by the anticoral-INS antivenom. Phylogenetic analyses using nd4, Cyt b, and 16S rRNA gene fragments showed a close relationship between M. dumerilii from Ecuador and Choco (Colombia), and within the M. dumerilii clade, a particularly close relationship between specimens from Antioquia and Santander. The venoms of M. dumerilii showed high overall similarity in their chromatographic profiles, with peaks corresponding to the three-finger toxin (3FTx) and phospholipase A2 (PLA2) protein families being predominant. Some differences were observed in the number of protein families identified in each venom, but the main fraction responsible for lethality in the venoms from Antioquia, Choco, and Santander was preserved. The commercial antivenom available in Colombia recognizes venom from all three regions. These general antigenic similarities between samples suggest that it may not be necessary to include M. dumerilii venoms from different geographic areas as immunogens for the production of antivenom against this species.